Safety and stability evaluation of the uranium tailings impoundment dam: Based on the improved AHP-cloud model - Xingwang Dai; Xianwei Wu; Yang Hong; Jiali Xie; Dongying Lin; Yifan Chen; Yong Liu (Journal of Radiation Research and Applied Sciences, 2022)
To solve the problem of safety and stability of the uranium tailings impoundment dam, based on the whole process of emergency management, the safety and stability evaluation system of the uranium tailings impoundment dam is established by using analytic hierarchy process (AHP) from the four aspects of design and construction, natural environment, operational stability and management, and the general weight of each evaluation index is calculated; the improved AHP-cloud model is introduced to obtain the basic evaluation cloud map for the safety and stability of the uranium tailing dam and two typical dams were evaluated in a large uranium tailings impoundment in southern China. The results show that the model can produce a more accurate evaluation of the safety and stability of the uranium tailings impoundment dam, and provide a reference for the subsequent decommissioning management work.